Análise da difusão espacial da COVID-19 no estado do Rio Grande do Sul, Brasil - Rodrigues, Maicon dos Santos (2024)
Appeared in 2019, in China, COVID-19 arrived in Rio Grande do Sul in February 2020, revealing major challenges in the detection, notification and treatment of cases, in addition to promoting intense disputes in the sphere of public administration in search of mitigating its impacts. in public health, human relations and the production process. In this context, this research analyzes the spatio-temporal dynamics of COVID-19 in the state of Rio Grande do Sul, in the period between February 2020 and January 2023, with the aim of understanding the pattern of spread of the disease and analyzing political decisions in managing this health crisis, seeking to discuss future strategies for new cases of spread of viral epidemics in the state. Geography has shown itself throughout history as an important instrument for articulating different areas of thought and, in the case of Health Geography, its spatial analysis techniques have been used in mapping since the 19th century for this purpose, when under the theoretical focus of Medical Geography. This research was designed based on public data on COVID-19 in the state of Rio Grande do Sul, collected on January 15, 2023. To process the data in order to understand the behavior of the pandemic in the state's territory, the method of Exploratory Analysis of Spatial Data, which made it possible to identify propagation patterns that, when crossed with the spatial structures of the territory and its demographic characteristics, offered fundamental reading keys to achieve the proposed objectives. The spatial behavior of the disease between epidemiological weeks nine and 36 showed the diffusion characteristics that predominated in different periods in the state. The observed expansion was influenced by intense flows from metropolitan regions, with a rapid advance to the north coast and, later, to the north region. The final completion of the saturation of contaminated municipalities occurred in the general West and South direction. This study finally revealed that demographic density and the complexity of economic connections were drivers of COVID-19 in the territory. The disease initially took hold in large and medium-sized municipalities, traveling along the federal highways BR290, 116 and 386, later spreading to other highways with lower traffic. COVID-19 as an actor deforming space and human relations showed the weaknesses and choices based on the logic of governmentality of the subject in the 21st Century.